Postmenopausal hormone therapy and cognition - McCarrey, Anna C. (Horm Behav, 2015)
Prior to the publication of findings from the Women’s Health Initiative (WHI) in 2002, estrogen-containing hormone therapy (HT) was used to prevent age-related disease, especially cardiovascular disease, and to treat menopausal symptoms such as hot flushes and sleep disruptions. Some observational studies of HT in midlife and aging women suggested that HT might also benefit cognitive function, but randomized clinical trials have produced mixed findings in terms of health and cognitive outcomes. This review focuses on hormone effects on cognition and risk for dementia in naturally menopausal women as well as surgically induced menopause, and highlights findings from the large-scale WHI Memory Study (WHIMS) which, contrary to expectation, showed increased dementia risk and poorer cognitive outcomes in older postmenopausal women randomized to HT versus placebo. We consider the ‘critical window hypothesis’, which suggests that a window of opportunity may exist shortly after menopause during which estrogen treatments are most effective. In addition, we highlight emerging evidence that potential adverse effects of HT on cognition are most pronounced in women who have other health risks, such as cerebrovascular disease or diabetes. Lastly, we point towards implications for future research and clinical treatments.